Evaluation of a genus reactive monoclonal antibody in rapid identification of Chlamydia trachomatis by direct immunofluorescence. Issue 4 (August 1985) - Alexander, I; Paul, I D; Caul, E O
Abstract : This study compared the direct visualisation of elementary bodies in urogenital smears by the direct immunofluorescence test with the isolation of Chlamydia trachomatis in McCoy cell cultures treated with cytochalasin B. C trachomatis was isolated from 41 (16.4%) of 250 unselected specimens in McCoy cell cultures treated with cytochalasin B. Of the 41 culture positive specimens 37 (90%) were diagnosed by direct visualisation of elementary bodies in the smears using the direct immunofluorescence test. Four specimens were positive by isolation only and a further seven were positive by the direct immunofluorescence test only. Overall the direct immunofluorescence test had a sensitivity of 90% and a specificity of 97%. The presence of red blood cells or mucus or the use of barrier creams did not appear to interfere with the normal visualisation of elementary bodies using the direct immunofluorescence test.